Stretchable/flexible silver nanowire Electrodes for energy device applications - Jung, Jinwook; Cho, Hyunmin; Yuksel, Recep; Kim, Dongkwan; Lee, Habeom; Kwon, Jinhyeong; Lee, Phillip; Yeo, Junyeob; Hong, Sukjoon; Unalan, Husnu Emrah; Han, Seungyong; Ko, Seung Hwan (Nanoscale, 2019)
Research on sustainable and high-efficiency energy devices has recently emerged as an important global issue. These devices are now moving beyond the form of a bulk, rigid platform to a portable, flexible/stretchable format that is easily available in our daily lives. Similar to the development of an active layer for the production of next-generation energy devices, the fabrication of flexible/stretchable electrodes for the easy flow of electrons is also very important. Silver nanowire electrodes have high electronic conductivity even in a flexible/stretchable state due to their high aspect ratio and percolation network structures compared to conventional electrodes. Herein, we summarize the research in the field of flexible/stretchable electronics on energy devices fabricated using silver nanowires as the electrodes. Additionally, for a systematic presentation of the current research trends, this review classifies the surveyed research efforts into the categories of energy production, storage, and consumption.
Keywords: Electronic conductivity; Energy productions; High aspect ratio; High-efficiency; Percolation networks; Research efforts; Research trends; Silver nanowires